The day I fired Alan Ladd and other World War II adventures - Hotchner, A. E. (University of Missouri Press, 2002)
"This memoir of A.E. Hotchner's World War II experiences explores a different side of the troubled war years. Hotchner, who grew up in St. Louis, was a rookie lawyer fresh out of Washington University Law School when the United States declared war. Like many others of his generation, he aspired to serve his country. He tried to enlist in the navy, first as a pilot and then as a deck officer, but he was rejected for faulty depth perception and flat feet, respectively. Drafted as a lowly GI into the air force branch of the army, he was accepted to bombardier school. But on the eve of his departure, he was ordered to write and perform in an air force musical comedy instead.